ROLE OF PANCHAKARMA CHIKITSA IN THE MANAGEMENT OF KLAIBYA: A CASE STUDY (AYUSHDHARA, 2017)
The most common reason for sexual dysfunction is the inability to maintain the erection for the whole sexual act. Impotency or Erectile dysfunction is defined as the inability to initiate and maintain the erection of sufficient rigidity that lost long enough to have successful sexual intercourse. It is a common disorder of variable severity. Good sex depends on many factors, physical, psychological, quality of relationship with partner. Sexual dysfunction which result in frustration, dissatisfaction and lower self esteem, affecting adversely the quality of life. The pathogenesis of Klaibya are, Bahu Doshavastha particularly the aggravated Vata. Hence in order to overcome Bahu Doshavastha Shodhana is essential, particularly Basti is the choice of treatment to overcome the aggravated Vata which in turn regulates the Manas. Further, Phalaghritha Uttarabasti is particularly designed to overcome the Dhatukshaya, Shukrakshaya and Jaravastha. Here a patient of Klaibya is treated with Virechana karma as purification is need, as the chronicity of disease is playing more part so Virechana is planned for Shuddhi karma. Uttarbasti is planned for the condition of Klaibya. Total 3 sittings of 7 day each of Uttar basti every month after Virechana is planned and patient receive good effect in erectile dysfunction. Panchakarma helps in rejuvenation and improve quality of life also. This condition has been elaborately described as 'Klaibya' in Ayurvedic classics and 'Erectile dysfunction' in modern texts. In the present article the effort is made to show the effect of Shodhana and Uttarbasti in a case of Klaibya. The following topic can be treated on bigger sample for research purpose.